Increased Cardiovascular Risk in Psoriatic Arthritis: Results From a Case-Control Monocentric Study - Degboé, Yannick; Koch, Richard; Zabraniecki, Laurent; Jamard, Bénédicte; Couture, Guillaume; Ruidavets, Jean Bernard; Ferrieres, Jean; Ruyssen-Witrand, Adeline; Constantin, Arnaud (Frontiers in Medicine, 2022)
Background. Psoriatic arthritis (PsA), is associated with increased cardiovascular morbidity and mortality. The aims of our real-life study were: to compare the prevalence of cardiovascular risk factors (CVRFs) and cardiovascular events (CVEs) among PsA patients with a control population; to evaluate the impact of correcting factors in equations that assess cardiovascular risk (CVR) in PsA; and to determine the percentage of patients who reach the LDLc target as indicated by the European guidelines. Methods. In this observational cross-sectional monocentric case-control study, we used a standardised procedure to systematically assess PsA patients aged 25 to 85 who met CASPAR criteria. Controls were extracted from the MONALISA study. We compared the prevalence of CVRFs, CVEs, the CVR and the percentage of patients reaching recommended LDLc target in both populations. The CVR was first assessed using SCORE and QRISK2 equations. Then, the SCORE equation was corrected by applying a 1.5 multiplication factor as recommended by EULAR for rheumatoid arthritis (SCORE-PsA) and the QRISK2 was corrected using the "rheumatoid arthritis" item (QRISK2-PsA). Results. 207 PsA and 414 controls were included. CVRFs and CVEs were more frequent in the PsA group. After controlling for age and gender, atherothrombotic disease was increased in the PsA population (SCORE p=0.002, QRISK2 p=0.001). Using the SCORE-PsA increased the percentage of patients with a high or very high CVR from 39.3% to 45.3% in the PsA group. Similarly, using the QRISK2-PsA increased the percentage of patients with a CVR≥10% from 44.9% to 53.2%. The percentages of PsA patients with high LDLc in the high and very high CVR groups were not significantly different from controls, despite a trend in favour of PsA patients. Of the 83 PsA with a QRISK2≥10%, only 22.9% were treated with statin versus 35.8% of the 134 controls. The QRISK2-PsA score did not alter these results. Conclusion. In real-life, patients with PsA have a higher prevalence of CVRFs, as well as a higher prevalence of MACEs compared to the general population. The CVR is higher in the PsA population than in the controls either using SCORE and QRISK2 equations or using SCORE- PsA and QRISK2-PsA equations.